Plasmodium vivax malaria: Is it still benign? - Alles, H.K.; Gunawardana, N.; Kularatne, S.A.M.; Arambepola, M.; Sheriff, M.H.R.; Carter, C.; Jayasinghe, S.; Mendis, K.N. (My University, 1996)
200 malaria patients were assessed in a prospective hospital-based project in Anuradhapura and Colombo, to study severe and complicated infections. Malaria was diagnosed either on microscopy or PCR. Severe and complicated infections were identified by accepted criteria and a numerical scoring method. 39 patients were positive for Plasmodiumvivax only, (17 males and 22 females, of whom 11 were pregnant; ages from 6 months to 59 years). 6 had severe and complicated malaria. 27 were uncomplicated and 6 were excluded because of possible co-existing disease. The severe and complicated group, in whom Plasmodium falciparum infection was excluded by PCR, included 4 patients with cerebral symptoms, 2 of whom died. In the group that was considered uncomplicated, 3 had Hb levels below 7 g/dl of whom one had features of hypersplenism, 3 had jaundice with raised liver enzymes, one had features suggestive of an ascending paralysis, one presented with abnormal behaviour, one had paroxysmal episodes of urticaria and two had multi-system involvement. 47% of patients had platelet counts less than 200000/ul. All pregnant women except one who was anaemic, were uncomplicated. All surviving patients responded well to antimalarials. P.vivax still remains the major species of malaria prevalent in Sri Lanka. A wide range of clinical presentations and complications following P. vivax infections were observed in this study. P. vivax is a parasite that is not known to sequester in deep organs. Our findings have implications on the pathogenesis of severe malaria.
Sri Lanka Medical Association - 109th Anniversary Academic Sessions :1996 ; 16p